The Interpolation of 1 Cor. 14.34–35 and the Reversal of the Name Order of Prisca and Aquila at 1 Cor. 16.19 - Fellows, Richard G. (Journal for the study of the New Testament, 2024)
Transpositions of large sections of text in New Testament manuscripts occurred only when omissions and chronological problems were ‘corrected’. It is argued here that the words commanding that women be silent in 1 Cor. 14.34–35, which appear elsewhere in Western manuscripts, were interpolated, and the interpolator probably created a textual variant at 14.37 and transposed Prisca and Aquila at 16.19 so that a woman would not host a church. Textual variants at 16.19 in the Western manuscripts are explicable if Prisca originally preceded Aquila here, as she does elsewhere. Second Timothy 4.19 is an early witness to Prisca’s precedence in 1 Corinthians.